Construction of the graph genomes of Takifugu provides novel insights into the genomic mechanisms of population structure and migratory traits - Rui-shi He; Rong Zhao; Jun-jie Lin; Yan Li; Xiang-zhu Kong; Jin-xuan Xu; Jing-hang Wu; Xing-jiang Bu; Yong-jun Zhang; Yang Sun (BMC Biology)
Abstract Background The genus Takifugu includes highly valued fish species known for their delicate flavor, making them popular in multiple countries. However, many species from this genus face significant threats. In order to better understand the genetic diversity and evolutionary dynamics of Takifugu, a syntelog-based pan-genome and graph genome were constructed using the data of seven Takifugu species. Results The analysis of 28,085 syntelog groups (SGs) composed of protein-coding genes revealed that only 57.3% of the SGs were shared among all individuals, whereas the remaining genes presented presence-absence variation (PAV) across the seven genomes. Using the graph genome as a reference, a population of 160 Takifugu individuals was analyzed, from which 20,133,471 SNPs, 4,606,141 Indels, and 152,200 SVs were identified. The gene flow analysis revealed directional gene flow from Takifugu bimaculatus and Takifugu flavidus to Takifugu oblongus. Notably, a 51-bp insertion in the ABCB9 gene differed significantly in frequency between the two migratory populations, suggesting the potential role of this gene in the migratory behavior of these species. Additionally, the expression profiles from 13 tissues or organs (brain, gallbladder, gill, gonad, heart, kidney, liver, muscle, pituitary, skin, spleen, stomach, and swim bladder) revealed a unique expression pattern in the liver, with the tissue-specific genes exhibiting evolutionary conservation to varying degrees. The highest proportion of core genes was found in the pituitary, whereas the lowest was found in the spleen. Conclusions This study provides comprehensive genomic resources that enhance the understanding of the genetic diversity and evolutionary dynamics of Takifugu species. The findings offer insights for research on both breeding and conservation of Takifugu.